Development and Standardization of the Abstract Reasoning Aptitude Test (ARAT) for Higher Secondary School Students - Chocha, Dinesh Rambhai; Dodiya, Malabhai B. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The present study aimed to develop and standardize the Abstract Reasoning Aptitude Test (ARAT) for higher secondary school students in Gujarat. Abstract reasoning, a critical component of cognitive intelligence, plays a significant role in academic achievement and future career success. The test was constructed following a rigorous process that included blueprint formation, item writing, expert validation, pre-piloting, pilot testing, and statistical analysis. The final version comprised 24 multiple-choice items assessing pattern recognition, analogy reasoning, series completion, and classification ability—independent of linguistic and cultural biases. A stratified sample of 2,640 students from 11 districts of Gujarat was selected, ensuring representation across gender, region (urban/rural), and school type. Item analysis confirmed acceptable difficulty and discrimination indices for all items. The reliability of the tool was established through multiple methods: Split-Half (r = 0.752), Test–Retest (r = 0.721), Cronbach’s Alpha (α = 0.726), and Guttman’s Lambda coefficients, all indicating strong internal consistency and temporal stability. Validity was ensured through expert judgment, construct alignment, and content relevance. Descriptive statistics, histograms, and cumulative frequency curves revealed a near-normal distribution of scores, and inferential statistics supported the tool’s discriminative ability across various demographic groups. Based on percentile norms, performance bands were established to interpret scores meaningfully. The finalized ARAT is thus a reliable, valid, and practical instrument for assessing abstract reasoning in the Indian educational context and can be used for student profiling, career guidance, and cognitive research.